2002
DOI: 10.3390/71000734
|View full text |Cite
|
Sign up to set email alerts
|

Silica Sulfuric Acid/ NaNO2 as a Novel Heterogeneous System for the Nitration of Phenols under Mild Conditions

Abstract: Nitrophenols can be obtained in moderate to high yields via nitrosation-oxidation of phenols with silica sulfuric acid, NaNO2 and wet SiO2 at room temperature. In situ generation of HNO2 and a radical cation mechanism via the nitrous acid catalyzed (NAC) pathway appear to be applicable to phenol nitration using these reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Application of inorganic nitrates such as bismuth nitrate [112,113] [Bi(NiO 3 ) 3 ], cerium ammonium nitrate [114] (CAN), sodium nitrite [115] (NaNO 2 ) and potassium nitrate (KNO 3 ) as nitrating agent were found to be more useful for nitration of aromatic compounds using silica gel as a solid support. Badgujar et al [116] recently reported the environmentally benign synthesis of aromatic nitro compounds using silica supported inorganic nitrates. This is an important step towards eco-friendly nitration process.…”
Section: Emerging Nitration Conceptsmentioning
confidence: 99%
“…Application of inorganic nitrates such as bismuth nitrate [112,113] [Bi(NiO 3 ) 3 ], cerium ammonium nitrate [114] (CAN), sodium nitrite [115] (NaNO 2 ) and potassium nitrate (KNO 3 ) as nitrating agent were found to be more useful for nitration of aromatic compounds using silica gel as a solid support. Badgujar et al [116] recently reported the environmentally benign synthesis of aromatic nitro compounds using silica supported inorganic nitrates. This is an important step towards eco-friendly nitration process.…”
Section: Emerging Nitration Conceptsmentioning
confidence: 99%
“…Application of inorganic nitrates such as bismuth nitrate [Bi(NiO 3 ) 3 ] [90,91], cerium ammonium nitrate [92], sodium nitrite (NaNO 2 ) [93] and potassium nitrate (KNO 3 ) [94] as nitrating agent were found to be more useful for nitration of aromatic compounds using silica gel as a solid support. These new nitrating systems will drastically reduce the use of acid in the nitration system, which will be an added advantage in terms of green and eco-friendly process.…”
Section: Dinitrogen Pentoxide: Versatile Nitrating Agent For Hemsmentioning
confidence: 99%
“…These problems have encouraged the search for other methods, especially alternating catalytic amounts of various solid acids with stoichiometric amounts of corrosive Brönsted acids and various nitrates or nitrites with nitric acid. Some of these methods include AcONO 2 [5], TfONO 2 [6], NaNO 3 /HCl with catalytic amounts of La(NO 3 ) 3 [7], trichloroisocyanoric acid/NaNO 2 /wet SiO 2 [8], Bi(NO 3 ) 3 .5H 2 O [9], Bi(NO 3 ) 3 /montmorillonite KSF [10], NaNO 3 /wet SiO 2 [11] , NaNO 2 /silica sulfuric acid [12], Mg(NO 3 ) 2 .6H 2 O [13], Cu(NO 3 ) 2 /clay [14], Fe(NO 3 ) 3 /clay [15], Fe(NO 3 ) 3 .9H 2 O/ionic liquid [16], VO(NO 3 ) 3 [17], some other metal nitrate/clay combinations activated by acetic anhydride [18], and more recently, ultrasound promoted nitration in ionic liquid with ferric nitrate and clayfen with good para selectivity [19], calcium nitrate/microwave [20], zirconyl nitrate [21] and PTSA/Ni(NO 3 ) 3 [22].…”
Section: Introductionmentioning
confidence: 99%